Human Artificial Intelligence Co Learning Dynamics in Hybrid Educational Ecosystems - Suardi (Kilau Publishing, 2026)
The digital transformation driven by artificial intelligence (AI) has reshaped the educational ecosystem toward hybrid learning; however, the dynamics of human–AI collaboration remain insufficiently understood, particularly in the Indonesian context where technological adoption is accelerating with uneven readiness. This study aims to analyze the dynamics of human–artificial intelligence co-learning, focusing on the interaction among students, lecturers, and AI systems in shaping learning engagement and regulation. This research employs a qualitative approach with an intrinsic case study design, involving 30 participants (24 students and 6 lecturers) selected through purposive sampling. Data were collected באמצעות semi-structured interviews and open-ended questionnaires and analyzed using thematic analysis. The findings reveal that AI functions as a cognitive assistant, feedback facilitator, and exploration partner, enhancing engagement and self-regulated learning, while also posing risks of reduced social interaction and reflective depth. Additionally, AI supports personalized learning, whereas the role of lecturers shifts toward strategic facilitators. The study concludes that the effectiveness of co-learning depends on the balance between technological integration, pedagogical readiness, and digital literacy, contributing to the development of adaptive and responsible hybrid learning models.